2020
DOI: 10.3390/math8071094
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Approach for the Heat Transfer Flow of Carboxymethyl Cellulose-Water Based Casson Nanofluid from a Solid Sphere Generated by Mixed Convection under the Influence of Lorentz Force

Abstract: The heat transfer of a carboxymethyl cellulose aqueous solution (CMC-water) based Casson nanofluid, flowing under the impact of a variable-strength magnetic field in mixed convection around a solid sphere, has been examined in this work. Aluminum (Al), copper (Cu), and silver (Ag) nanoparticles were employed to support the heat transfer characteristics of the host fluid. A numerical approach called the Keller-box method (KBM) was used to solve the governing system for the present problem, and also to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 44 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Diverting from the vertical plate approach, recent studies considered the convection boundary layer flow over a horizontal circular cylinder, solid sphere, etc. For example, some researchers [19][20][21][22] studied the convection boundary layer flow in nanofluid past a solid sphere and horizontal circular cylinder. More studies on the boundary layer flow in a nanofluid over cylinder are given in the following references [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Diverting from the vertical plate approach, recent studies considered the convection boundary layer flow over a horizontal circular cylinder, solid sphere, etc. For example, some researchers [19][20][21][22] studied the convection boundary layer flow in nanofluid past a solid sphere and horizontal circular cylinder. More studies on the boundary layer flow in a nanofluid over cylinder are given in the following references [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that increasing the Casson parameter reduces local skin friction, velocity, or temperature and increases the local Nusselt number. The other researchers that have been investigating are Ullah et al, 11 Gbadeyan et al, 12 Rasool et al, 13 Alwawi et al, 14,15 to name a few. In recent years, the nanofluid has been extended to hybrid nanofluid to enhance the fluid characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Dogonchi et al [44] numerically studied the impacts of a magnetic field and joule heating on a nanofluid over a stretching plate considering Brownian motion. Alwawi et al [45,46] modeled the magneto-free/mixed convection flow of Casson nanofluid over a solid sphere. The reader may also refer to Refs.…”
Section: Introductionmentioning
confidence: 99%